Nozzle Tester Teaching Tool to Enhance Learning Outcomes in Conventional Diesel Engine System for Light Vehicles - Hidayatulloh, Choirul Fatah; Khumaedi, Muhammad; Anis, Samsudin (Journal of Vocational and Career Education, 2025)
The nozzle tester, which is commonly used in the automotive engineering program at SMK N 1 Kedungwuni, is in a leaking condition, limiting its effectiveness in supporting learning and consequently affecting student learning outcomes. This issue is the main reason for conducting research on the development of a nozzle tester using a recycled jack, aimed at enhancing the learning of conventional diesel engine systems. This study employs a Research and Development (R&D) approach with the ADDIE model for development. The research method used is a pretest-posttest group design. The findings of the study include: (1) the developed teaching tool was considered feasible by media and subject matter experts, with content validity ratio (CVR), content validity index (CVI), and percentage of agreement (PA) analyses; (2) product trials showed a high level of effectiveness, demonstrated by the Independent Sample t-Test, where the N Gain Score resulted in a significant (2-tailed) value; and (3) the reproducibility coefficient (Kr) and scalability coefficient (Ks) both indicate that the application of the nozzle tester in the conventional diesel engine system learning process is very practical. The conclusion of this study is that the nozzle tester can significantly improve the learning outcomes of conventional diesel engine systems.